Mixture design approach as a tool to study in vitro flavor release and viscosity interactions in sugar-free polyol and bulking agent solutions - Siefarth, Caroline; Tyapkova, Oxana; Beauchamp, Jonathan; Schweiggert, Ute; Büttner, Andrea; Bader, Stephanie (Food Research International, 2011)
Flavor release from mixtures of maltitol, erythritol, polydextrose and oligofructose dissolved in water at concentrations of 43% (w/w) was investigated to analyze possible interactions between the viscous matrix and the volatiles using an experimental mixture design in combination with data analysis and response modeling tools. The dynamic release of four flavor compounds (cis-3-hexenol, benzaldehyde, ethyl butanoate and butyl isovalerate) from the matrices at 37 degrees C was determined by headspace analyses using proton-transfer-reaction mass spectrometry (PTR-MS). The aim of the present study was to understand the complex release mechanisms from high-viscosity polyol and bulking agent solutions for the intention of conducting further studies on flavor release from sugar-free confectionary products. Each of the non-volatiles had a significant effect (p < 0.05) on flavor release with regression coefficients (R(2)) between 0.72 and 0.93 for the release parameters I(max), t(1/2), and Delta c/Delta t, and 0.99 for viscosity. However, the magnitude of influence varied between the bulking agents and polyols due to their different molecular weights. A clear correlation between viscosity of the solutions and flavor release was found, revealing complex matrix-volatile interactions in the highviscosity solutions. The release of all investigated flavor compounds decreased when the viscosity of the solutions increased. Therefore, it is assumed that the flavor release is significantly influenced by the nonvolatiles when a critical concentration (c*) is exceeded. Interactions between the sugar substitutes were found to affect the viscosity of the matrices, whereas flavor release was not affected by interactions between the polyols and bulking agents investigated. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Critical concentration (c*); Experimental mixture design; Flavor release; Matrix-flavor-interactions; PTR-MS; Viscosity